STRATEGI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) DALAM MEWUJUDKAN MAL PELAYANAN PUBLIK YANG BERKUALITAS DI KABUPATEN GROBOGAN - Avrilia Pratiwi; Puji Astuti (Journal of Politic and Government Studies, 2026)
This study aims to analyze the strategy of the Grobogan Regency Investment and One-Stop Integrated Services Agency (DPMPTSP) in realizing a quality Srikandi Public Service Mall (MPP), and to identify supporting and inhibiting factors in its implementation. The research employed a qualitative approach with data collected through interviews, observation, and documentation. The analysis focused on three main stages of Strategic Management: formulation, implementation, and evaluation. The results show that DPMPTSP developed a comprehensive strategy through a demand-driven approach, supported by Public Satisfaction Survey (SKM) data, Focus Group Discussions (FGDs), and priority service analysis. During implementation, the strategy was realized through service integration across 33 agencies, service standard enforcement, and technology utilization such as digital queuing systems and electronic SKM. During evaluation, the 2025 SKM score reached 92.054 (very good category), though service quality gaps were identified among units. Key supporting factors include leadership commitment, modern facilities, and professional staff. Inhibiting factors include technological system instability, cross-agency discipline issues, high queue volumes, and challenges with incomplete public documents.